Perlindungan Hukum Pemegang Rahasia Dagang Untuk Menjamin Kepastian Hukum (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Trade secrets are a form of intellectual property that have economic value and are confidential in nature. Legal protection for trade secrets is essential to provide legal certainty for their holders and to promote a healthy business competition environment. This article discusses the legal protection provided to trade secret holders in Indonesia under Law No. 30 of 2000 on Trade Secrets, and analyzes the effectiveness of such protection in ensuring legal certainty. Using a normative legal approach, this paper demonstrates that while legal frameworks exist, there remain various challenges in their implementation, particularly regarding proof and enforcement. Therefore, it is necessary to strengthen protection mechanisms and increase business actors' awareness of the importance of maintaining trade secrets.